การควบคุมการฟุ้งกระจายฝุ่นถ่านหินบริเวณโม่บดด้วยม่านน้ำที่มีประจุไฟฟ้าและม่านอากาศ - ชัญกฤช จันทพิมพะ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research is a study of the control of coal dust diffusion in the crusher by electrical charged water curtain and air curtain. Tested with a test sink 0.6 meters wide and 1.2 meters long and 1.6 meters high, which has the characteristics and the ratio of the sink of the crusher 14 times. Which will be equipped with 3 types of coal dust diffusion control systems which are water curtain system, air curtain system and local exhaust ventilation system within the system, there is a corona charging to spray water for treat coal dust. By considering the speed of the air curtain and the suction speed of the air in the local exhaust ventilation system that is most suitable for controlling diffusion in mathematical models with the ESI-CFD program. The results of the calculation with the program will then be tested with the test sink to see the characteristics of diffusion and amount of coal dust produced.